PROJECT ESTIMATION OF CORPORATE IDENTITY, PUBLIC CHARACTERISTICS AND PUBLIC PERCEPTION TOWARD THE HOTEL WEBSITE AT FIVE STARS HOTEL IN JAKARTA - Wibowo, Wihartantyo Ari; Prasetyawati, Dea (Emerging Markets : Business and Management Studies Journal, 2014)
PROJECT ESTIMATION